(untitled) (World Bulletin of Management and Law, 2024)
Human Resources (HR) departments play a pivotal role in contemporary business operations, serving as a strategic partner in talent management, organizational development, and fostering a culture of innovation and productivity. This article explores the multifaceted functions of HR within businesses, emphasizing its significance in shaping workforce dynamics, enhancing employee engagement, and driving organizational success